DESAIN OF ACOUSTIC SANDWICH COMPOSITE FROM FOAM CONCRETE AND PALM FIBER - Devya Kartika Devya; Mursal Mursal; Zulkarnain Djalil (Jurnal Natural, 2018)
The purpose of this research were to investigate the influence of palm fiber composition and the number of hole cavities was varied with design Acoustic Sandwich Composite on sound absorption of acoustic panel. Acoustic panel were made of palm fiber as core and foam concreate as skin upper layer and bottom layer where there is a hole cavity on skin upper layer. Composition and the number of hole cavities was varied from 1 to 3 kg and the number of hole cavities from 25 to 81 hole. Sound absorption measurement was conducted by using reverberation room method based on ISO-354 (2003) with pink and white noise as sound source.The results showed that sample thickness affect acoustic absorption value effectively shifted at low frequencies, as in this research the best sound absorption occurs in panel with composition palm fiber most widely 3 kg, but coeffesient absorpsi value effective is in the range 250 Hz and use the number of hole cavities at skin upper layer of each sample effectively cause sound absorption coeffisient value increased, for both pink and white noise from sound source.Keyword : acoustic panel, foam concrete, palm fiber, sandwich composite, and absorption coefficient